Pulse-width Control of Electro-reaction Engines for a Station-keeping of Land-survey Satellite on Sun-synchronous Orbit. (2017) - Somov, Yevgeny; Starinova, Olga; Butyrin, Sergey
Abstract: A small information satellite which may be placed on an orbit with altitude from 600 up to 1000 km is considered. The satellite attitude and orbit control system contains a strap-down inertial navigation system, cluster of four reaction wheels, magnetic driver and a correcting engine unit with eight electro-reaction engines. Problems on the design of algorithms for control of the satellite spatial motion on sun-synchronous orbit are studied.